Perception of transient nonspeech stimuli is normal in specific language impairment: evidence from glide discrimination - D. V. M. Bishop; C.V. Adams; K Nation; S Rosen (2005)
Twenty 9- to 12-year-olds with specific language impairment (SLI) were compared with 18 age-matched controls on auditory discrimination tasks, using a three-interval, two-alternative forced-choice format. The first task used minimal word pairs in silence and in noise. Nonspeech tasks involved discriminating direction of frequency glides and had two versions: (a) the glide moved from 500 to 1500 Hz, and duration was adaptively decreased; (b) all glides lasted 250 ms, and the frequency range was adaptively modified until a threshold was reached. Control and SLI groups did not differ on the glide tasks. Around half the children in both groups accurately discriminated 20 ms glides. There was a small but significant group difference on the speech-in-noise task, and scores were weakly related to literacy level. Perception of brief, transient, nonspeech stimuli is not abnormal in the majority of school-aged children with SLI.